2023
DOI: 10.1111/cns.14103
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‐3131 derived from endothelial cells with KRAS mutation promotes EndMT by targeting PICK1 in brain arteriovenous malformations

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…24 During the EndMT, certain endothelial markers may be lost or retained in parallel to the acquisition of mesenchymal markers and morphology. [25][26][27][28] Li et al [29][30][31][32] recently reported that KRAS mutations regulate the EndMT in cerebral arteriovenous malformations, and KLF4 was described as a key determinant of the EndMT in cerebral cavernous malformations. Although the EndMT contributes to a variety of cerebrovascular disorders, its role in MMD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 During the EndMT, certain endothelial markers may be lost or retained in parallel to the acquisition of mesenchymal markers and morphology. [25][26][27][28] Li et al [29][30][31][32] recently reported that KRAS mutations regulate the EndMT in cerebral arteriovenous malformations, and KLF4 was described as a key determinant of the EndMT in cerebral cavernous malformations. Although the EndMT contributes to a variety of cerebrovascular disorders, its role in MMD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The endothelial‐to‐mesenchymal transition (EndMT) is a process through which endothelial cells acquire mesenchymal phenotypes, while losing their endothelial characteristics 24 . During the EndMT, certain endothelial markers may be lost or retained in parallel to the acquisition of mesenchymal markers and morphology 25–28 . Li et al 29–32 …”
Section: Introductionmentioning
confidence: 99%